2020
DOI: 10.1021/acsinfecdis.0c00019
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/Pharmacodynamic Determination and Preclinical Pharmacokinetics of the β-Lactamase Inhibitor ETX1317 and Its Orally Available Prodrug ETX0282

Abstract: Increasingly resistant Enterobacteriaceae have emerged as a health threat in both hospital and community settings. Infections of the urinary tract, once often treated with oral agents in the community, are requiring increased hospitalization and use of intravenously administered agents for effective treatment. These isolates often carry extended spectrum βlactamases (ESBLs) and carbapenemases that necessitate the need for an inhibitor to cover a broad range of β-lactamases. ETX1317 is a novel diazabicyclooctan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Cefpodoxime (CPD) emerged as the lead β-lactam candidate. 30 Its approved use as an orally bioavailable proxetil ester prodrug to treat UTI infections was also aligned with our potential target product profile. A fixed 1:2 ratio of cefpodoxime/ETX1317 was utilized as the testing paradigm for antimicrobial susceptibility.…”
Section: Results and Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Cefpodoxime (CPD) emerged as the lead β-lactam candidate. 30 Its approved use as an orally bioavailable proxetil ester prodrug to treat UTI infections was also aligned with our potential target product profile. A fixed 1:2 ratio of cefpodoxime/ETX1317 was utilized as the testing paradigm for antimicrobial susceptibility.…”
Section: Results and Discussionmentioning
confidence: 83%
“…Liver and intestinal S9 subcellular fractions (Xenotech) from rat and human tissue were diluted to a protein concentration of 0.8 mg/mL in 100 mM potassium phosphate buffer, pH 7.4, and preincubated in a 37 °C water bath for 5 min prior to addition of 10 μM (final) of compound of interest. Serial aliquots were removed at 0, 2, 5, 10, 20, 40, and 60 min and quenched in acetonitrile with internal standard prior to LC/MS/MS 30 to determine concentrations of prodrug. First order degradation half-lives were determined from the slope of the log–linear plots of the depletion data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ETX0282 ( 14) in combination with cefpodoxime proxetil, which is a prodrug of cefpodoxime approved for the treatment of antibiotic-resistant Enterobacteriaceae urinary tract infection, is a promising oral therapy for infections caused by ESBLproducing and carbapenem-resistant Enterobacteriaceae. [103][104][105][106] Undoubtedly, the broad-spectrum of activity of durlobactam (13) and ETX0282 ( 14)-or its active form ETX1317 (15)-represents a huge advance in restoring the efficacy of carbapenems in infections caused by the WHO priority pathogens. However, like avibactam these compounds are also inefficient against metallo--lactamases (Table 1).…”
Section: Overview and Spectrum Susceptibility Of Non-boron-based -Lactamase Inhibitorsmentioning
confidence: 99%
“…The bioavailability of ETX0282 observed from the phase 1 studies has not been reported. In preclinical species (rat, dog, and monkey) it showed at least 78% bioavailability [ 64 ].…”
Section: Novel β-Lactam and β-Lactamase Inhibitorsmentioning
confidence: 99%